Determination of PAHS in Soil, Cassava and Processed Cassava Meal (Fufu) from Selected Communities in Ohaji Egbema, Imo State, Nigeria - Nkwocha C. J.; Okereke J. N.; Mgbemena I. C.; Okpechi N. J.; Okwara K. K. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
This study investigates levels of Polycyclic Aromatic Hydrocarbons (PAHs) in soil, cassava tubers from farmlands and processed cassava meal (fufu) in Ohaji/Egbema, Nigeria. Impact of PAHs on soil and cassava portends adverse effect on health of people. Ten different samples of soil, cassava and fufu collected from ten different villages in Ohaji/Egbema Local Government Area, and a positive control from Umuguma, a distant village located in Owerri West Local Government Area were examined for PAHs contamination using Gas Chromatography (GC) system equipped with Flame Ionization Detector (DC/FID). The results obtained showed the presence of all USEPA Target PAHs in different concentrations in mgkg 1 . Soil samples observed from Ekwugba and Etekwuru had PAHs concentration at 1.1x 10 2mg/kg; and1.28mg/kg respectively ranging from the least to the highest. Cassava sample from Etekwuru recorded the highest PAHs value of (1.7x10-2mg/kg), followed by cassava sample from Asaa with PAHs value of (9.0x10-3mg/kg) while cassava from Ekwugba had the least PAHs value of (1.0x10-3mg/kg). PAHs level obtained from soil samples had no correlation to that from cassava tubers harvested from such farmlands. From the study, the PAHs levels in most samples were above ATSDR (2021) accepted limit between 0- 0.1mg/kg. The results as presented in table 3 show that there is no significant difference in the level of PAHs in fufu from Ohaji/Egbema and control location. It is therefore recommended that affected areas should be remediated before being use as farmlands for cultivation of edible crops.